Stabilization of an amylase from Neurospora crassa by Immobilization on Highly Activated Supports - Tavano, Olga L. (2008)
The amylase from Neurospora crassa is an interesting enzyme, having higher stability than amylase from Aspergillus oryzea under a broad range of pH values. Moreover, the N. crassa enzyme may be immobilized on different supports with good retention of enzyme activity. The best stabilizations were achieved using Eupergit C 250 L or glyoxyl agarose, with which the enzyme remained fully active at 60°C for 24 h while the soluble enzyme remained about 17%. The glyoxyl agarose immobilized enzyme had high thermostability, high optimal temperature (65°C) and broad pH/activity profile, suggesting that this enzyme has potential for food and industrial applications for starch modification. Copyright © Taylor & Francis Group, LLC.